Complications associated with intravenous midazolam and fentanyl sedation in patients undergoing minor oral surgery - Saiso, Krittika (J Dent Anesth Pain Med, 2017)
BACKGROUND: Anxiety control remains an important concern in dental practice. We evaluated the incidence, nature, and sequelae of complications during and after minor oral surgeries performed under intravenous midazolam and fentanyl sedation using the titration technique. METHODS: The medical records of patients who had undergone minor oral surgeries under moderate intravenous midazolam and fentanyl sedation at our institution between January 1, 2015 and December 31, 2015 were retrospectively evaluated. Age, sex, body mass index, medical history, American Society of Anesthesiologists (ASA) classification, indications for sedation, amount of sedative used, surgical duration, and recovery time were evaluated for all patients. RESULTS: In total, 107 patients aged 9–84 years were included. ASA class I and class II were observed for 56.1% and 43.9% patients, respectively. Complications associated with sedation occurred in 11 (10.2%) patients. There were no serious adverse events. Oxygen saturation reached 95% during the procedure in six patients; this was successfully managed by stimulating the patients to take a deep breath. Two patients exhibited deep sedation and one exhibited paradoxical excitement. After the procedure, one patient experienced nausea without vomiting and one exhibited a prolonged recovery time. The surgical procedures were completed in all patients. Obesity was found to be significantly associated with sedation-related complications. CONCLUSIONS: Our results suggest that complications associated with intravenous midazolam and fentanyl sedation using the titration technique for minor oral surgeries are mostly minor and can be successfully managed with no prolonged sequelae.